Estimating the Potential Annual Welfare Impact of Innovative Drugs in Use in Switzerland - Pavic, Matea; Pfeil, Alena M.; Szucs, Thomas D. (Frontiers in Public Health, 2014)
Expenditures of health care systems are increasing from year to year. Therefore, this study aimed to estimate the difference in costs and benefits of innovative pharmaceuticals launched 2000 onwards compared to standard treatment on the national economy of Switzerland in 2010. The approach and formula described in the pilot study by Tsiachristas et al. in 2008, which analysed the situation of welfare effects in the Netherlands, served as a model for our own calculations. A literature search was performed to identify cost-utility or cost-effectiveness studies of drugs launched 2000 onwards compared to standard treatment. All parameters required for the calculation of welfare effects were derived from these analyses. The base-case threshold value of a quality-adjusted life year (QALY) was set to CHF 100`000. Overall, 31 drugs were included in the welfare calculations. The introduction of innovative pharmaceuticals since 2000 onwards to the Swiss market led to a potential welfare gain of about CHF 781 million in the year 2010. Univariate sensitivity analysis showed that results were robust. Probably because of the higher benefits of new drugs on health and quality of life compared to standard treatment, these drugs are worth the higher costs. The literature search revealed that there is a lack of information about the effects of innovative pharmaceuticals on the overall economy of Switzerland. Our study showed that potential welfare gains in 2010 by introducing innovative pharmaceuticals to the Swiss market were substantial. Considering costs and benefits of new drugs is important.